Analisis Perkiraan Tingkat Pelayanan Jalan (Studi Kasus Rencana Tol Dalam Kota Jakarta Ruas Bekasi Raya) - Nidea Novitasari; Tri Sudibyo (Departemen Teknik Sipil dan Lingkungan, IPB University, 2020)
In 2017, Jakarta was ranked as 7th most congested city in the world. To overcome the problem of congestion in Jakarta, the Government implements the construction of road infrastructure through 6 toll roads inside Jakarta City, but the construction causes pros and contra regarding the effects of induced demand. This research aimed to analyze the service level of Bekasi Raya road on existing and toll roads in Jakarta City and analyzing Bekasi Raya road performance after the operation of the toll road and the off ramp impact of toll road. The analysis were conducted based on Indonesian Road Capacity Manual 1997, the Greenshield model, and the Highway Capacity Manual 2000. The result showed that the level of road service in segment 1 was C for Bekasi and D for the Pulogadung direction. In segment 2 the level of service was E for both directions, and in segment 3 the level of service was C. The level of the toll road service was C for both directions. The toll roads construction would increase the level of road service to C and reduce vehicle volume of 64,1% in Bekasi direction and 45,2% for Pulogadung (Jakarta) direction. The off ramp impact was the the toll road would not experience significant congestion until 2035.